2019
DOI: 10.1111/cxo.12812
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic visual acuity and refractive errors in elite football players

Abstract: Dynamic visual acuity of forwards is lower than that of other players. Twenty-five per cent of players who need to use visual correction to practice sports actually use it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
(39 reference statements)
1
30
1
2
Order By: Relevance
“…In the article by Jorge et al [14], they used the same software as in our study, COI-SV, for the analysis of dynamic visual acuity where 147 high-level futsal players were analyzed. In this article, they concluded that dynamic visual acuity varies by playing position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article by Jorge et al [14], they used the same software as in our study, COI-SV, for the analysis of dynamic visual acuity where 147 high-level futsal players were analyzed. In this article, they concluded that dynamic visual acuity varies by playing position.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the limitations of our study, the software used in our study has been used in another published research [14]. The decision to use this software is that COI-SV can perform both diagnostic tests and optometric treatments with a specific focus on sports vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports vision encompasses comprehensive visual assessment, sports-specific enhancement of visual performance, and ocular protection for athletes, aiming to improve athletes’ performance [ 6 , 7 ]. Studies have demonstrated that athletes have better visual abilities than non-athletes [ 8 ] in terms of larger fields of peripheral vision [ 9 , 10 , 11 ], better dynamic visual acuity [ 12 , 13 ], and more accurate depth perception [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Football is a team sport in the performance of which skilled cooperation plays an important role. (Jorge & Fernandes, 2019). Sport promotes good values such as cooperation, sportsmanship, mutual respect and fair play.…”
Section: Introductionmentioning
confidence: 99%